A identidade que revela uma origem: um estudo sobre duas universidades comunitárias e confessionais brasileiras - Sá, Daniella Guimarães Bergamini de (2019)
In the current context of higher education in Brazil, the Confessional Community Universities (CCU) have in their values an important factor of differentiation before other Higher Education Institutions (HEIs). But rather than differentiating themselves from other institutions, values are part of recognizing the identity of a CCU. The general purpose of this dissertation is to identify the identity elements that characterize two renowned Brazilian community and confessional HEIs. This dissertation therefore analyzed, through collective and individual understanding, the recognition of the identity of two Brazilian CCUs – Mackenzie Presbyterian University (UPM) and the Pontifical Catholic University of Rio de Janeiro (PUC-RJ). Some HEIs survive and stand out, hence the choice of these two institutions. Values are assumed to be a revealing element of institutional origins. To this end, the methodology adopted allowed differentiating values and institutional principles from the groups that make up these two institutions. The adopted method was qualitative, aiming to explore the establishment of the relationship between education and religion, besides describing the characteristics of the studied HEIs. The research was developed in five stages, the first one, collecting data and information from secondary sources in order to take a about the types of universities and the organization of higher in Brazil. In the second stage, it was developed a document analysis of the Institutional Development Plan (IDP) of the two researched Universities, in order to understand how they are strategically organized and what is the proposed progression for the next five years. The third stage was the exploratory field research, where we visited and photographed the particularities and evidence within the campuses to prove the existence of the physical presence of the values professed by the HEIs. In the fourth stage, a questionnaire was prepared to better understand the general manifestation of the problem, where 5,900 employees, teachers and students answered how they felt about the environment and the coexistence in the institutions and the environment they offer. In the fifth and last stage, the rectors of the two universities were interviewed. The questions elaborated dealt with the identity issue, the contributions of the UCC and the challenges they perceived in contemporary times. The survey results indicate that both the deans and the internal community list the same set of factors, with a consensus about the identity elements of the researched institutions